Evaluation of the influence of earthworm on compost quality of empty fruit bunch and cow dung / Mohamad Aidil Paimon - Paimon, Mohamad Aidil (Faculty of Plantation and Agrotechnology, 2015)
Evaluation of the influence of earthworm on compost quality of empty fruit bunch and cow dung was conducted for this study. The potential of the earthworm as the agent of the composting towards the physical changed during the process and the nutrient content at the end of the product were examined. The experimental was designed in a completely randomized design with three different treatment (different densities of earthworm) and control treatment (without earthworm) (T1) in three replications. The physical changes of pH and temperature during composting process were recorded 12 days interval same as the nutrient content of nitrogen, phosphorus, potassium, calcium and magnesium was recorded . Data analysis was carried out by using SPSS software and Microsoft Excel. The result obtained in this study indicates that there are no significant in the physical changes . However, there has significant in nutrients content toward the different densities of earthworm. It is concluded that potential of earthworm clearly gives a good effect on compost quality, however, different earthworm densities contribute the different nutrients content for each type of nutrients. Furthermore, the influence of the earthworm in the compost quality still promising to have significant effect compare to composting without the earthworm.